Exploring The Meaning of Existence in The Thought of Jean Paul Sartre with Abd Al-Rahman Badawi - Karima, Dewi Sofiyatul (Center for Research and Publication (PUSLITPEN), UIN Syarif Hidayatullah Jakarta, 2023)
Existentialism is a philosophical doctrine that has the basis of human existence, then enters the field of literature as one of the best intellectuals and arts to reach humans. Jean Paul Sartre (1905-1980) as the triumphant bearer who declared himself an atheist existentialist. The existence of man precedes his essence as man determines his own nature freely. Based on man's freedom in creating his own essence, Sartre formulated